Recovery from anhydrobiosis in the tardigrade Paramacrobiotus experimentalis: Better to be young than old and in a group than alone - Nagwani, Amit Kumar; Melosik, Iwona; Kaczmarek, Łukasz; Kmita, Hanna (Heliyon, 2024)
Desiccation-tolerant organisms can survive dehydration in a state of anhydrobiosis. Tardigrades can recover from anhydrobiosis at any life stage and are considered among the toughest animals on Earth. However, the factors that influence recovery from anhydrobiosis are not well understood. The study aimed to evaluate the effect of sex, age, the presence of other individuals and the combination of the number and duration of anhydrobiosis episodes on the recovery of Paramacrobiotus experimentalis. The activity of 1200 individuals for up to 48 h after rehydration was evaluated using analysis of variance (ANOVA). Age was the main factor influencing return to activity, followed by the combination of number and duration of anhydrobiosis episodes, influence of the presence of other individuals, and sex. More individuals returned to activity after repeated short than repeated long anhydrobiosis episodes and older individuals were less likely to recover than younger individuals. In addition, when compared to single animals, the presence of other individuals resulted in higher number of active animals after dehydration and rehydration. The effect of sex was significant, but there was no general tendency for one sex to recover from anhydrobiosis better than the other one. The results contribute to a better understanding of the anhydrobiosis ability of Paramacrobiotus experimentalis and provide background for full explanation of molecular, cellular and environmental mechanisms of anhydrobiosis.